Multivariate analysis on gross participation rate in primary school or equal by indicators of gender, residence and expenditure in indonesia year 2018, 2019 and 2020 - Bahtiar, Reza Syehma; Retnawati, Heri (Universitas Malikussaleh, 2021)
Primary school education is an important factor for the success of the next level education. Several changes have been made to the education system in Indonesia to expand access of education in rural areas, improve the quality of education, building initiatives since 2001. In this study, the method used was Multivariate to explore the relationship between several independent variables, i.e. gender, residence and expenditure groups. Prerequisite tests performed showed that the data were normally distributed. The results of this study indicate that in the Hierarchical Cluster analysis, four clusters were found in number of gross participation rate (APK) of primary schools or equal in Indonesia year 2018, 2019 and 2020. The hypothesis test showed that gender, residence and expenditure group has no significant effect on APK of primary schools or equal students. This indicates that in year 2018, 2019 and 2020, primary schools or equal students have received education evenly in ratio of gender, residence and expenditure group.